Terpenoid composition and antioxidant activity of extracts from four chemotypes of Cinnamomum camphora and their main antioxidant agents. (22nd November 2021) - Luo, Qingyun; Tian, Zhengfeng; Zheng, Tiefeng; Xu, Sun; Ma, Yuandan; Zou, Shuzhen; Zuo, Zhaojiang
Abstract: Cinnamomum camphora (L.) J. Presl can produce an abundance of terpenoids, and has four main chemotypes: linalool, eucalyptol, camphor, and borneol. Antioxidant activity and the chemical composition of extracts from the four chemotypes were investigated during spring (May), summer (July), and autumn (November) with the aim of developing natural antioxidants using suitable chemotypes of C. camphora in suitable seasons, together with their main terpenoids. The main antioxidant terpenoids were identified. The four chemotype extracts showed strong scavenging activity against 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) and 2, 2′‐azino‐bis(3‐ ethylbenzothiazoline‐6‐sulphonic acid) (ABTS) free radicals as well as O2 – · and ·OH in July, due to the fact that their terpenoid content was at its highest during this month. Among the four chemotypes, the strongest scavenging activity was mainly detected in the linalool chemotype extracts, which had the highest terpenoid content. Among the ten main terpenoids in C. camphora extracts, ocimene, linalool, β ‐pinene, longifolene and eucalyptol showed stronger scavenging activity against DPPH free radicals, and ocimene exhibited the strongest scavenging activity. Extracts from the four chemotypes of C. camphora and their main terpenoids have the potential for development as natural antioxidants, with summer as the best season, linalool chemotypes as the optimum choice, and ocimene as the optimum compound. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd